Arthropod populations in a sub‐arctic environment facing climate change over a half‐century: variability but no general trend. Issue 5 (9th March 2022) - Andersson, Göran; von Proschwitz, Ted; Fägerström, Christoffer; Green, Martin; Smith, Henrik G.; Lindström, Åke
Abstract: Dramatic declines of some arthropod populations have recently received a lot of attention. Identified declines have mainly been attributed to changes in agriculture, climate, pathogen prevalence and light pollution, as well as cross‐regional effects of, e.g., drifting pesticides. However, the overall picture is complex and debated, and there is a need for systematically collected long‐term data, not least from areas relatively unaffected by humans. We monitored the abundance of arthropods (mainly insects) in subalpine birch forest in Swedish Lapland over a period of 53 years (1968–2020), in an area comparatively unaffected by human activities. Arthropod abundance was assessed by yearly systematic counts on 24, 000 birch shoots, in the second half of June. Animals were categorised into 17 different groups directly upon counting, dependent on taxonomy and life stage (imago, larva). Overall, there was no significant change in arthropod numbers. Nor did estimates of the total biomass of arthropods (using group‐specific indices of the mass of individuals) show any significant trend. Accordingly, there are no signs that the arthropod abundance or biomass on birch in this subarctic study site has gone through the same declines as have been reported from sites in other habitats. The reason may be that the impact of factors identified worldwide as drivers of arthropod declines so far are small or non‐existent because of the low human population density in this area. Abstract : We counted the number of arthropods of 17 different taxa over a period of 53 years (1968–2020) in subalpine birch forest in Swedish Lapland. There was no significant change in total arthropod numbers over 53 years, nor in our estimate of total arthropod biomass. The reason for the lack of a long‐term trend may be that the factors identified worldwide as drivers of arthropod declines are mainly lacking because of the low human population density in this area.